Road Infrastructure Concession Practice in Europe - Bousquet, Franck; Fayard, Alain (World Bank, Washington, DC, 2014)
In a road infrastructure concession, a public authority grants specific rights to a private, or semi-public company to construct, overhaul, maintain, and operate infrastructure for a given period. By contract, the public authority charges that company with making the investments needed to create the service at its own cost, and to operate it at its own risk. The price paid to the company comes from the service's users, the public authority, or both. In 1999, out of roughly 51,000 kilometers of European motorways, about 17,000 kilometers (33 percent) were concessioned - 16,400 kilometers by toll, and 670 kilometers by shadow toll (design, build, finance, and operate arrangements). Of these, 73 percent are managed by the public sector, and 27 percent by private companies. State-owned companies have been important in European motorway concessions. Systems vary among countries, for example, in how they share risks between the concession authority, and the concession company. As the motorway network has grown denser, attributing commercial risk has become more difficult. Increasingly, public authorities must play a greater regulatory role. Already, bad experiences have made the private sector reluctant to bear the commercial risk. Ant the commercial risk is sometimes too great to be carried by the concession company alone. Commercial risk should be controlled by mechanisms incorporated in the contract, but control of the commercial risk must not eliminate incentives. In addition to safeguarding the community's interests, the public concession authority, must increase citizen awareness about concession decisions, to ensure their social acceptability. Formulas for determining toll charges, differ through Europe. So do criteria for selecting concession companies. In 1999, the main criteria used were these: 1) the amount of public subsidy required; 2) the credibility of the financial arrangements; 3) the project's technical quality; 4) the operating strategy, and price policy; and, 5) the reputation of the concession company (whether it has a construction company among its shareholders, for example). The increasingly frequent use of private funding, must be taken into account when defining the training required by personnel responsible for monitoring the concessions.